A fungus (Trametes pubescens) resists cadmium toxicity by rewiring nitrogen metabolism and enhancing energy metabolism - Liu, Jing; Fu, Pengcheng; Wang, Li; Lin, Xiuying; Enayatizamir, Naeimeh (Frontiers in Microbiology, 2022)
As a primary goal, Cadmium (Cd) is a heavy metal pollutant which is readily adsorbed and retained in rice, it becomes a serious threat to food safety and human health. Fungi have attracted interest for its ability to remove heavy metals from environment, although the underlying mechanisms on how fungi defend against Cd toxicity are still unclear. In this study, a Cd-resistant fungus Trametes pubescens was investigated. The pot experiments of rice seedlings colonized with T. pubescens showed that it could significantly enhance rice seedling growth and reduce Cd accumulation on rice tissues. Furthermore, integrated transcriptomic and metabolomic analyses were used to explore how the T. pubescens would reprogram its metabolic network against ROS caused by Cd toxicity. Based on multi-omic data mining results, we postulated that under Cd stress, T. pubescens was able to up regulate both the MAPK and phosphatidylinosital signaling pathways, which enhanced the nitrogen flow from amino acids metabolism through glutaminolysis to α-ketoglutarate (α-KG), one of the entering points of TCA cycle within mitochondria, it thus increased the production of energy equivalents, ATP and NADPH for T. pubescens to resist oxidative damage. This study can enable a better understanding of the metabolic rewiring of T. pubescens under Cd stress, it can also provide a promising potential to prevent the rice paddy fields from Cd toxicity.